2009
DOI: 10.1111/j.1748-5967.2009.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Braula orientalis Örösi (Diptera: Braulidae) in honeybee colonies with tobacco smoke under semiarid conditions

Abstract: In the present study, bee colonies were smoked with tobacco smoke in order to evaluate the monthly changes in the numbers of worker bees, the infestation rates of worker bees and queens with bee lice, and the annual average honey production per colony. In July of each year, 12 colonies were smoked with tobacco smoke; the remaining hives not smoked with tobacco smoke served as the control. The results indicated that the applications of tobacco smoke during July gave rise to an impressive reduction in the Braula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Despite bee lice being discovered inside bee colonies all year long, Al-Ghzawi et al (2009) observed a decline in the infestation rate after December and during the spring, hitting its lowest level in April. Zaitoun and Al-Ghzawi (2008) reported that the infestation rate of B. coeca increased rapidly in May.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite bee lice being discovered inside bee colonies all year long, Al-Ghzawi et al (2009) observed a decline in the infestation rate after December and during the spring, hitting its lowest level in April. Zaitoun and Al-Ghzawi (2008) reported that the infestation rate of B. coeca increased rapidly in May.…”
Section: Discussionmentioning
confidence: 92%
“…A recent experimental study revealed bee louse to be an obvious cause of a decrease in the number of worker bees and honey production ( Al-Ghzawi et al , 2009 ), despite some previous accounts not attributing any negative effects to the presence of B. coeca on the honey bees ( Akratanakul, 1986 ).…”
Section: Discussionmentioning
confidence: 99%
“…The temperature of the syrup should not exceed 49 °C. For the treatment of Nosematose, fumigillin is added to the syrup at a ratio of 1/844 and given in early spring and late autumn feeding [13][14][15][16][17][18][19][20].…”
Section: Studymentioning
confidence: 99%
“…There is a method to eliminate the proliferation of the parasite, based on the hypothesis that the insect only has one generation per year, so it is enough to uncap the honey boxes present in the hive during the larval period of the parasite, in order to break their biological cycle [13][14][15][16][17]. Braula coeca is an external commensal that is located on the body surface of the bee, more precisely on the back, between the junction of the thorax and abdomen.…”
Section: Epizootiologymentioning
confidence: 99%
“…The damage that these insects cause to the hive occurs in two moments, the first during their development, when the larvae dig tunnels by digging the wax, and the second, in their adult phase, when they are on the queens in high frequency and number, being able to reach to the area of the proboscis and thus with its movements irritate the queen and cause regurgitation of the food content on which it feeds. Furthermore, the presence of lice on the queen's body causes discomfort that leads to a considerable decrease in oviposition, resulting in a decrease in the number of larvae and therefore the family [13][14][15][16][17].…”
Section: Epizootiologymentioning
confidence: 99%